Diet of Rhinella scitula (Anura, Bufonidae) in the Cerrado, Brazil: the importance of seasons and body size - Franciéle P. Maragno; Franco L. Souza (Revista Mexicana de Biodiversidad)
The aims of this study were (1) to analyze the diet of Rhinella scitula in different seasons (dry and rainy), and (2) to examine resource partitioning among sexes and body-size categories. Individuals were collected during active searches along a riverbank in the Serra da Bodoquena National Park, Brazil. Formicidae, followed by Coleoptera and Isoptera, had the highest importance index values for males, females, and all individuals combined. Diet composition was similar between males and females. Larger individuals consumed larger prey, although they fed on small prey as well. Similar-sized individuals had high dietary overlap. Smaller individuals had a diet as broad as larger individuals, although composed of different items. Formicidae was the most common prey item for animals collected in both the dry and rainy seasons, but was more important in the rainy season. During the dry season, R. scitula remained closer to the edge of the water bodies and showed the widest dietary niche, represented by similar importance index values.